Kewenangan Impeachment Oleh DPRD Terhadap Kepala Daerah - Yoga Partamayasa (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2020)
The application of impeachment in Indonesia is different from the application of impeachment in another states since there is a system of impeachment of the head of district. As a form of the implementation of district autonomy system there is an existence of executive and legislative branches in the regions. And in line with the authority received by the regional’s institutions there is also an initiative to do a surveillance mechanism for the executive and legislative branches in the regions which reflect the surveillance mechanism for the executive branch in the central government. The existence of this regulation stimulates debates and differentiation of interpretation on at least 3 main problems which are first regarding the interpretation of validity of district’s legislative impeachment authority, Second regarding the working relation between Legislative institution and Legislative institution in districts, and third regarding the responsibility of the incumbency of the head of district and its legal consequences. This problem stimulates debates and differentiation of academic interpretation. Therefore, there are much that can be observed regarding the differentiation of stipulations to the extend of the technical process from the impeachment mechanism as a form of an enforcement to trim down chaos of law (rechtsverwarring). Legal reform is a form of enforcement to revitalize the structure of constitutional system in Indonesia. Hopefully, with that revitalization Hopefully the Nusantara good governance can be achieved and can bring our nation to a better future. Keywords: Impeachment; Governmental Institution; Local Government Abstrak Penerapan impeachment di Indonesia berbeda dengan di negara lain karena terdapat sistem impeachment kepala daerah. Sebagai salah satu bentuk pelaksanaan sistem otonomi daerah, terdapat lembaga eksekutif dan legislatif di daerah. Sejalan dengan kewenangan yang diterima oleh lembaga daerah juga terdapat inisiatif untuk melakukan mekanisme pengawasan terhadap eksekutif dan legislatif di daerah yang mencerminkan mekanisme pengawasan eksekutif di pusat. Adanya Perpres terkait ini memicu perdebatan dan diferensiasi tafsir atas minimal tiga masalah pokok yaitu pertama tentang penafsiran keabsahan kewenangan pemakzulan DPRD, kedua, tentang hubungan kerja antara lembaga legislatif dan lembaga legislatif di daerah, dan ketiga, tentang tanggung jawab. tentang jabatan bupati dan konsekuensi hukumnya. Masalah ini memicu perdebatan dan diferensiasi interpretasi akademis. Oleh karena itu, banyak hal yang dapat dicermati mengenai diferensiasi ketentuan hingga perluasan proses teknis dari mekanisme impeachment sebagai bentuk penegakan untuk meredam kekacauan hukum (rechtsverwarring). Reformasi hukum merupakan salah satu bentuk penegakan hukum untuk merevitalisasi struktur ketatanegaraan di Indonesia. Semoga dengan revitalisasi itu semoga pemerintahan yang baik nusantara bisa tercapai dan bisa membawa bangsa kita menuju masa depan yang lebih baik. Kata Kunci: Pemakzulan; Institusi Pemerintah; Pemerintah Daerah